Scalable, Optimal Flow Routing in Datacenters via Local Link Balancing - Sen, Siddhartha; Shue, David; Ihm, Sunghwan; Freedman, Michael (Proc. 9th Conference on Emerging Networking Experiments and Technologies (CoNEXT), 2013)
Datacenter networks should support high network utilization. Yet today’s routing is typically load agnostic, so large flows can starve other flows if routed through overutilized links. Even recent proposals like centralized scheduling or end-host multi-pathing give suboptimal throughput, and they suffer from poor scalability and other limitations. We present a simple, switch-local algorithm called LocalFlow that is optimal (under standard assumptions), scalable, and practical. Although LocalFlow may split an individual flow (this is necessary for optimality), it does so infrequently by considering the aggregate flow per destination and allowing slack in distributing this flow. We use an optimization decomposition to prove LocalFlow’s optimality when combined with unmodified end hosts’ TCP. Splitting flows presents several new technical challenges that must be overcome in order to interact efficiently with TCP and work on emerging standards for programmable, commodity switches. Since LocalFlow acts independently on each switch, it is highly scalable, adapts quickly to dynamic workloads, and admits flexible deployment strategies. We present detailed packet-level simulations comparing LocalFlow to a variety of alternative schemes, on real datacenter workloads.
12 pages